Minimizing left ventricular stroke work with iterative learning flow profile control of rotary blood pumps. (January 2017) - Rüschen, Daniel; Prochazka, Frederik; Amacher, Raffael; Bergmann, Lukas; Leonhardt, Steffen; Walter, Marian
Abstract : Highlights: An iteratively learning flow controller for rotary blood pumps is proposed. It is used to track flow profiles that minimize the left ventricular stroke work. Feasibility demonstrated in hybrid mock circulatory loop experiments. Abstract: Rotary blood pumps are gaining importance in the successful treatment of advanced heart failure. However, the application of fixed pump speeds is discussed controversially. Since the natural heart delivers pulsatile flow, many physicians presume that pulsatile pumping provides therapeutical advantages. To address this, we combine the technical advantages of continuous flow devices with the supposed physiological advantages of pulsatile flow. We present an iterative learning control (ILC) strategy for continuous flow ventricular assist devices that minimizes the left ventricular stroke work (LVSW). For that, a comprehensive nonlinear model for rotary blood pumps that is used for simulation and controller design is introduced. The controller is tested using a hardware-in-the-loop cardiovascular system simulator with a Medos deltastream DP1 blood pump. The tracking performance of the proposed ILC approach is compared to a benchmark controller that uses additional sensor information, both controllers significantly reduce the residual LVSW compared to the fixed speed case. In addition to decreasing ventricular load, the proposed ILC strategy can be used as an inner control loop to any physiological controller that sets reference flow profiles. The introduced controller might be useful for the investigation of effects of various pulsatile flow patterns independent from the type of VAD in future in vivo studies. The targeted manipulation of physiological quantities such as the residual cardiac work has the potential to considerably improve ventricular assist device therapy.